PERAN PEREMPUAN DI KECAMATAN GROGOL KABUPATEN SUKOHARJO - Baroroh, Charunie (PKn Progresif, 2006)
The women is state asset that have key to bring into the ideal success of freedom Indonesia. Women human resource must be developed to run life together with man. It must be socialized it?s the knowledge that is as future concrete cpncept. The ideal life, better life not only in the world but also better life at the better after-beyond tomorrow (fidunya hasanah wa fil akhirati hasanah waqina ?adzaban nar).